索利图德湖 ：荒野中的个人 - Rolston, Holmes, 1932-2025, author; N. Pub. B. HLJP., publisher (Colorado State University. Libraries, 1999)
Lake Solitude, in remote Rocky Mountain National Park, offers a solitary traveler a place to seek continuities and discontinuities with nature, a communion of opposites. To travel into the wilderness is to go into what one is not, so that in returning to its natural complement, mind grasps itself. Nature thrusts humans into an immense solitude, but that is her grandest gift.
Lake Solitude: the individual in wildness
This was originally published as: "Lake Solitude: The Individual in Wildness," Main Currents in Modern Thought 31 (1975): 121-126.
Translated into Chinese by Liu Er 刘耳.
The original English version is online at http://hdl.handle.net/10217/37105.
Keywords: wildness; solitude; spiritual energy; meditations; Lake Solitude; Rocky Mountain National Park